SAT0767-HPR Physical activity maintenance and digital health interventions in people with rheumatoid arthritis: patient and healthcare professionals' perspectives. (15th June 2017) - Simmons, R; Lempp, H; Galloway, J; Bearne, L
Abstract : Background: Physical Activity (PA) improves health and function in people with Rheumatoid Arthritis (RA) but people with RA commonly fail to meet recommended PA levels. Digital Health Interventions (DHIs) are delivered through digital media to facilitate behaviour change, such as maintaining PA. To date, little is known about the perceptions of people who have RA or their healthcare professionals (HCPs) about the factors that influence PA and the desirability and perceived suitability of using DHI to support PA maintenance. Objectives: To explore RA patients' and HCPs' perceptions of the factors that influence PA maintenance as well as their views on the use of DHIs to support sustained PA. Methods: Adults aged >18 years with established RA were recruited from two inner-city NHS hospitals. Semi-structured interviews, using a topic guide developed a priori, were conducted by one researcher either face-to-face or by telephone until data saturation of themes was reached. HCPs working at one NHS inner-city hospital, who self-reported >3 months experience managing RA patients attended one semi-structured focus group, facilitated by two researchers and informed by a topic guide. The interviews and focus group were audio-recorded, transcribed verbatim and the data analysed thematically. Themes were corroborated by a sample of participants and an independent researcher. Results: 11 patients were recruited between January-May 2016 (five females; mean age 58 years [standard deviation 17 years]). Five themes were identified from the interviews: 1) Balancing the benefits of activity with the costs; 2) Gaining knowledge about safe and effective PA; 3) Disease control; 4) The environment matters; and 5) Interaction of person, disease and DHI. Patient participants were largely aware of the benefits of PA but wanted more information about safe PA. Ongoing PA was informed by participants balancing the benefits of PA with concerns about aggravating symptoms. Good symptoms control facilitated PA but severe and unpredictable symptoms and unsuitability of exercise facilities were perceived as barriers to PA maintenance. Patient participants mostly stated that DHIs were a desirable and acceptable adjunct to supporting PA maintenance. The focus group was conducted with six HCPs (two physiotherapists, two rheumatologists, one podiatrist and one medical student). Two themes were identified 1) Inactivity demands a proactive response by HCPs and 2) DHIs have potential to support PA, but "there is no panacea". HCP participants universally agreed that PA was beneficial and that it was important to support ongoing PA through education and multimodal interventions, including DHIs. Conclusions: Disease control, knowledge and environmental factors influence PA maintenance in people with RA, who balance the perceived benefits with the potential costs of PA. HCPs recognise the need to proactively support PA maintenance. DHIs offer a potentially useful and acceptable tool to support PA maintenance. Disclosure of Interest: R. Simmons Grant/research support from: NIHR MRes fellowship, H. Lempp: None declared, J. Galloway: None declared, L. Bearne: None declared